Local economic development through export-led growth: the chilean case - César, Andrés Manuel (2024)
We study the causal impact of export growth on Chilean local economic development during 2000–2006 by exploiting spatial and temporal variations in local exposure stemming from the interaction of past differences in industry specialization across local labor markets and the evolution of tariffs cuts and exports across industries. We find that growing exports implied a significant reduction in labor informality and labor income gains in more exposed local markets, driven by job creation and wage growth in the formal sector. These effects concentrate on senior skilled workers. Exposed locations also exhibit a greater relative decline in the poverty rate.